AN OVERVIEW OF AUGMENTED REALITY AND ITS APPLICATION IN THE FIELD OF INTERIOR DESIGN - Egizbyev, M.N.; Bekmanova, G.T.; Akhaeva, Z.B.; Tolegenova, G.B.; Zakirova, A.B. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2022)
In today’s growing and evolving world of new technologies, where new innovations are regularly emerging to make our lives easier, augmented reality is one of the fastest growing fields, with applications in almost every industry. In almost all industries, it will be seen as one of the key technologies of the future. It is safe to assume that interior design will be one of the biggest industries in which AR will revolutionise. As we are living in the era of digitalization and technology, and these days every industry is more or less connected or becoming connected with new technologies, and even those industries that categorically could not be connected with technology are nowadays being integrated with new technologies. This review looks at augmented reality and how it can be applied to interior design. The AR approach to interior design can also improve the design outcome, as the collaboration between the designer and his or her client becomes much easier. Various computer vision concepts are used to provide an interactive and immersive experience for the user. These can be realised by using plug-ins in game engines such as Unity 3D or Android Studio, which are used to develop an AR application.